Prediction of Compaction Properties of Clayey Soils Stabilized With Calcium Carbide Residue - Sandamali, D.M.T.U.; Sampath, K.H.S.M.; Ranathunga, A.S. (University of Jaffna, 2022)
The use of Calcium Carbide Residue (CCR) for soil stabilization results in changes of the properties of natural soil. In terms of compaction properties, the addition of CCR reduces the maximum dry density (MDD) of clayey soils while increasing the optimum moisture content (OMC). This paper describes a multivariate linear regression model and a multivariate polynomial regression model which can predict the MDD, and OMC of clayey soils stabilized with CCR, respectively. In both models, the compaction properties of the natural soil and the CCR mix proportion are used as independent variables and the developed models can be used to study any clayey soil which can be classified as CH or CL according to the unified soil classification system (USCS). From the statistical analysis, it is found that the models are capable of accurately predicting the compaction properties (i.e., MDD and OMC) of clayey soils stabilized with different CCR dosages with a prediction accuracy of ±5%. Therefore, the developed correlations can be effectively used as an indirect approach to estimate the improved compaction properties of soil in the process of soft ground improvement using CCR.
Keywords: Calcium Carbide Residue; Compaction; Clayey soils; Regression analysis; Maximum dry density; Optimum moisture content